Footballer Fabio - Randall, Ronne (Ladybird London, 2004)
"Footballer Fabio" tells the story of a young boy named Fabio who dreams of becoming a great footballer. As he trains hard and practices his skills, he faces challenges and learns valuable lessons about teamwork, perseverance, and sportsmanship. The story inspires readers to pursue their passions and highlights the joy of playing the game with friends.